2010
DOI: 10.5012/bkcs.2010.31.5.1336
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Cobalt-Iron Prussian Blue Analogues Nanotubes by CTAB Soft-Template Method

Abstract: Three cobalt-iron Prussian Blue Analogues (PBAs) nanotubes contained with different alkali metal cations of K, Rb or Cs, respectively, were prepared by using cetyltrimethylammonium bromide (CTAB)/ethanol-water micelles as soft templates. The products were characterized by energy-dispersive X-ray spectroscopy (EDS), X-ray diffraction (XRD), transmission electron microscopy (TEM) and scanning electron micrograph (SEM), which confirmed the composition of the substances and their unique nanotube structures. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…01-071-3740), TEM, and EDX results for particles collected from the heavy oil matrix and heat treated at 300 °C under N 2 atmosphere to removed adsorbed organics are shown in Figure a–c. It is clear from the figure that nickel nanoparticles were successfully formed in the heavy oil matrix, and heat treatment under nitrogen did not seem to affect their identity. The mean crystalline size calculated by applying Scherrer’s equation from the XRD peak at 2θ = 44.6° was 17 nm. The mean particle diameter calculated from the TEM images of 40 particles was 22 ± 5 nm, which is not very different from the XRD estimate.…”
Section: Resultsmentioning
confidence: 95%
“…01-071-3740), TEM, and EDX results for particles collected from the heavy oil matrix and heat treated at 300 °C under N 2 atmosphere to removed adsorbed organics are shown in Figure a–c. It is clear from the figure that nickel nanoparticles were successfully formed in the heavy oil matrix, and heat treatment under nitrogen did not seem to affect their identity. The mean crystalline size calculated by applying Scherrer’s equation from the XRD peak at 2θ = 44.6° was 17 nm. The mean particle diameter calculated from the TEM images of 40 particles was 22 ± 5 nm, which is not very different from the XRD estimate.…”
Section: Resultsmentioning
confidence: 95%
“…Zhao and co-worker synthesized nanoscale cobalt-iron PBAs with shapes of hollow, cube, and sphere in w/o microemulsions containing nonionic surfactant polyoxyethylen tertocthlphenyl ether (Triton X-100) and cationic surfactant cetyltrimethyl ammonium bromide (CTAB). [7][8][9][10][11] It is well known that the dynamic behavior is one of the most important factors in producing nanoparticles, however the studies of the kinetics for such reactions were rarely reported due to the difficulties in determining the concentration of species in the reaction and the complexitiy of the reaction mechanism. [12][13][14] The cobalt-iron PBAs can be synthesized from the reaction between potassium ferricyanide (K 3 Fe(CN) 6 ) and cobalt chloride (CoCl 2 ).…”
Section: Introductionmentioning
confidence: 99%